New assemblage of cingulates from the Quebrada de Los Colorados Formation (middle Eocene) at Los Cardones National Park (Salta Province, Argentina) and the Casamayoran SALMA problem at Northwestern Argentina - Fernicola, Juan Carlos (2021)
In the Eocene deposits of Northwestern Argentina, the order Cingulata was recognized in the sedimentary levels of the upper and lower sections of the Lumbrera (Salta Province), Geste (Catamarca and Salta provinces), Quebrada de Los Colorados (Salta Province), and Casa Grande (Jujuy Province) formations. The traditional biochronological scheme associated the Geste Formation to the Mustersan SALMA (37.3–35.4 Ma; Priabonian), the lower section of the Lumbrera Formation to the Vacan Subage (44–46 Ma; Lutetian) of the Casamayoran SALMA, and the fossiliferous levels of the remaining units to the Barrancan Subage (39–42 Ma; Bartonian) of the Casamayoran SALMA. Nevertheless, recent dating obtained for the top of the lower section of the Lumbrera Formation supports a new geochronological framework for Northwestern Argentina, which changes the temporal assignation of the taxa that have been collected in this section, going from the Vacan Subage to the Itaboraian SALMA, affecting also the biochronology of the Quebrada de Los Colorados and the upper section of the Lumbrera formations, which are now constrained between 46 and 40 Ma (Lutetian). In this contribution, we present a new cingulate assemblage based on osteoderms collected in the basal levels of the Quebrada de Los Colorados Formation at Los Cardones National Park, Calchaquí Valley (Salta, Northwestern Argentina), which is constituted by a new taxon plus Pucatherium parvum and Parutaetus punaensis. In addition, we discuss all the Eocene cingulate associations reported for Northwestern Argentina taking into consideration the new geochronological framework.